Heavy Metal Contamination Along the Nigde-Adana Highway, Turkey - GURHAN YALCIN, M.; BATTALOGLU, RIFAT; ILHAN, SEMIHA; TUMUKLU, ALI; TOPUZ, DERVIS (Asian Journal of Chemistry, 2010)
This study was conducted on the route of D805 and D750 state highways and TEM E90 motorway connecting the Nigde and Adana cities in central and southern Anatolia. The aim of study is to determine the heavy metal contamination in upper level of soil along the D805, D750 and TEM highways. Heavy metal concentrations were measured with Spectro-Xepos Benchtop X-Ray Fluorescence Spectrometer. Results of heavy metal analyses on soil samples reveal a significant contamination. It was determined that heavy metal accumulation is closely associated with traffic intensity. The heavy metal ranges and averages for soil samples at D805, D750 and TEM E90 roads were found as 16980-62790 / 37907.76, 17.8-98.6 / 43.62, 20-217 / 71.65, 56.5-405.9 / 165.55, 3.6-5.1 / 4.33, 75.5-596.2 / 175.76, 169-1167 / 554.9, 24-79 / 39.47, 316-1289 / 764.97, 1830-5048 / 3088.23, 6.8-15 / 8.56, 22-26 / 23.89, 2.8-63.4 / 13.86 mg/kg for Fe, Cu, Pb, Zn, Cd, Ni, Cr, Co, Mn, Ti, Sn, Mo and As elements, respectively. In this study, all heavy metal contents to have a toxic effect.